Sodium danshensu attenuates cerebral ischemia–reperfusion injury by targeting AKT1 - Gao, Qing; Deng, Hao; Yang, Zhengfei; Yang, Qiuyue; Zhang, Yilin; Yuan, Xiaopeng; Zeng, Miao; Guo, Maojuan; Zeng, Wenyun; Jiang, Xijuan; Yu, Bin (Frontiers in Pharmacology, 2022)
Previous studies have shown that sodium Danshensu (SDSS) has great potential in attenuating heart ischemic reperfusion injury. However, its role in CIRI and specific target proteins need to be further elucidated. In PC12 cells which were exposed to oxygen-glucose deprivation/reoxygenation (OGD) environment, SDSS significantly improved cell viability, meanwhile reducing LDH leakage and cell apoptosis level. The results of HuprotTM human protein microarray and network pharmacy indicated AKT1 was the main target of SDSS. Functional experiments showed SDSS intervention evidently increased the phosphorylation level of AKT1 and its downstream regulator mTOR. Binding sites of SDSS to AKT1 protein were confirmed by Autodock software and Surface plasmon resonance experiment. Our data demonstrated that SDSS perfectly suit to PH domain of SDSS, and the binding sites were likely ASN-53, ARG-86, and LYS-14. The rescue experiments revealed that knockdown of AKT1 significantly blocked the role of SDSS and activation of AKT1 could evidently increase the effect of SDSS. Finally, we investigated the curative effect of SDSS in the rat CIRI model. Administration of SDSS significantly reduced CIRI-induced necrosis and apoptosis. The present study proved that SDSS attenuated necrosis and apoptosis rate after CIRI by binding and activating AKT1 protein.